Determinants of Corporate Dividend Policy: A Factorial Analysis - Purba, Jamian; Dian Sulistyorini Wulandari; Khansa Naelil Muna (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Dividend Payout Ratio serves as a crucial determinant in deciding whether a company will distribute its end-of-year profits to shareholders through dividends or retain them to augment capital for future investments. This study focuses on assessing the impact of company size and profitability on the dividend policy of entities operating in the property, real estate, and building construction service sectors, as listed on the Indonesia Stock Exchange. The research, spanning a three-year period from 2018 to 2020, relies on secondary data, employing purposive sampling to select 24 out of 72 service companies based on the availability of complete financial reports. Utilizing multiple linear three reanalyses, the research reveals that company size does not significantly influence dividend policy, while liquidity positively correlates with dividend policy. Conversely, profitability shows no discernible effect on dividend policy. The study concludes that the liquidity ratio plays a pivotal role in shaping dividend policy. In contrast, factors like firm size and Return On Assets do not exert a significant impact on the Dividend Payout Ratio